The protective effect of resveratrol against cyclosporine A-induced oxidative stress and hepatotoxicity. (2nd November 2021) - Bingul, Ilknur; Olgac, Vakur; Bekpinar, Seldag; Uysal, Mujdat
Abstract: The immunosuppressive agent cyclosporine A (CsA) has hepatotoxic potential. Increased reactive oxygen species (ROS) formation is among the causes leading to hepatotoxicity. This study aimed to investigate the effect of resveratrol (RES) on CsA-induced oxidative stress and hepatotoxicity in rats. Rats were treated with RES (10 mg/kg/day; i.p.) for 14 days. CsA (25 mg/kg/day; s.c.) was given during the last seven days together with RES. Serum alanine aminotransferase and aspartate aminotransferase activities together with hepatic histopathological examinations were performed. ROS, thiobarbituric acid reactive substances (TBARS), advanced oxidation protein products (AOPPs), ferric reducing antioxidant power, and glutathione levels as well as superoxide dismutase, and glutathione peroxidase activities were measured in the liver tissue. RES ameliorated histopathological changes and decreased hepatic ROS, TBARS, and AOPP levels significantly. However, antioxidant parameters did not change in CsA-treated rats. Our results indicate that RES treatment may be effective in decreasing CsA-induced oxidative stress and hepatotoxicity.